2005
DOI: 10.1158/1055-9965.epi-04-0720
|View full text |Cite
|
Sign up to set email alerts
|

The T393C Polymorphism of the Gαs Gene (GNAS1) Is a Novel Prognostic Marker in Bladder Cancer

Abstract: The G protein GAs pathway is linked to proapoptotic signaling in cancer cell lines. To assess the role of the GNAS1 locus encoding GAs as a genetic factor for disease progression of transitional cell carcinoma (TCC) of the bladder, we genotyped the synonymous T393C polymorphism in 254 patients with TCC (minor allele frequency: 0.43) to examine a potential association between genotypes and disease progression. Using Kaplan-Meier estimates to calculate 5-year probabilities of follow-up, we could show that progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
81
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 43 publications
12
81
2
Order By: Relevance
“…The T393C polymorphism is silent, not changing the amino acid of the affected codon in exon 5 of the GNAS1 gene. However, we have previously shown that the GNAS1 polymorphism is associated with altered Gas mRNA expression in different tissues (35). We found that the TOC substitution at position 393 changes the mRNA folding structures (37).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The T393C polymorphism is silent, not changing the amino acid of the affected codon in exon 5 of the GNAS1 gene. However, we have previously shown that the GNAS1 polymorphism is associated with altered Gas mRNA expression in different tissues (35). We found that the TOC substitution at position 393 changes the mRNA folding structures (37).…”
Section: Discussionmentioning
confidence: 77%
“…Tukey's HSD test is one of the several methods of ensuring that the chance of finding a significant difference in any comparison (under a null model) is maintained at the alevel of the test and therefore preserves 'family-wise type I error'. Since the T393C polymorphism shows a genedose effect (35)…”
Section: Discussionmentioning
confidence: 99%
“…26 Increased Gas expression may cause increased cAMP concentrations, 29 comparable to activating mutations of GNAS1, which also increase IL-6 levels. 30 IL-6 is a major mediator of osteoclast formation and bone resorption in aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…Definitely, it has been shown in different tissues, that Gas mRNA expression is increased in TT genotypes. 26 Yang et al 27 reported that the T393C polymorphism is not linked to an other, possibly functional polymorphism in linkage disequilibrium, and Frey et al 28 showed in an in silico analysis that the altered mRNA expression is most likely caused by altered mRNA stability. The T393C SNP and the associated alteration of Gas expression could influence bone and macrophage physiology as well as IL-6 expression levels and, therefore, may also alter the time to aseptic loosening.…”
mentioning
confidence: 99%
“…Gas signaling is of particular interest in the study of endophenotypes of schizophrenia, because increased activity of this protein has been noted in the striatum and leukocytes of patients with schizophrenia (Memo et al, 1983;Avissar et al, 2001). Further, a polymorphism, which results in increased mRNA expression of Gas (Frey et al, 2005), has recently been genetically linked to schizophrenia (Minoretti et al, 2006). Interestingly, transgenic mice expressing a constitutively active isoform of Gas (Gas*) show decreased PPI (Gould et al, 2004).…”
Section: Introductionmentioning
confidence: 99%